To Safety and Beyond! A Scoping Review of Human Factors Enriching the Design of Human-Robot Collaboration - Jasper Vermeulen; Glenda Caldwell; Müge Teixeira; Alan Burden; Matthias Guertler (Interaction Design and Architecture(s))
This scoping review explores human factors that enrich the design of Human-Robot Collaboration (HRC) beyond the traditional focus on ergonomics and safety. As Industry 5.0 shifts towards a human-centric perspective, understanding the multifaceted interactions within socio-technical systems becomes crucial. The review investigates diverse fields, including design, psychology, and engineering, to identify human factors influencing the successful integration of Collaborative Robotics. The research findings confirm the need and potentiality of using the holistic lens of human factors to illuminate human-centric needs in HRC designs. Moving beyond quantitative measures, the study advocates for qualitative insights to inform the design of HRC and enhance worker conditions through individualised and contextualised experiences of collaborating with cobots. The findings contribute to advancing the understanding of HRC’s complexity and underscore the significance of user-driven perspectives in future research and design efforts.